Research of opportunities to improve the quality of educational process and infrastructure of the university - E. V. Krasnov; I. V. Semenov; E. V. Sumarokova (Вестник университета)
Modern marketing approach to improving the educational process and infrastructure of the university in order to enhance its competitiveness has been studied. A model of the marketing educational environment of the university has been proposed. The need for diagnostics of "bottlenecks" in the work of the university’s functional units in the transition period to the knowledge paradigm of the country’s economic development has been actualized. The experience of the Department of Marketing of the State University of Management in conducting annual marketing research to study the possibilities of improving the quality of educational process and infrastructure of the University using the method of student team consulting has been outlined. The distinctive features of this method and the specifics of its application in the spring semester of2020 with an emphasis on virtual teams in the context of the COVID-19 pandemic have been described. Debatable issues and prospects for further scientific research in this area have been formulated.